Asuhan Keperawatan Pada Lansia Dengan Arthritis Rheumatoid: Nursing Care for the Elderly With Rheumatoid Arthritis - Solehudin; Saiful Gunardi; Irma Herliana (Open Access Jakarta Journal of Health Sciences, 2022)
Introduction: Rheumatoid arthritis is the most common autoimmune disease in the community. This disease is characterized by inflammation of the lining of the synovium of the joint. It can cause long-term joint damage, prolonged pain, loss of function and disability. Objective: This study aims to determine nursing care for the elderly with a medical diagnosis of rheumatoid arthritis. Methods: The research design used a case study with a nursing process approach. The sampling technique used is convenience sampling. The sample in this study was Mrs. U age 70 years. The research was conducted at the Jagakarsa Public Health Center, Jakarta in May 2021. The data was collected by means of interviews, observations, and documentation studies. The research instrument is a gerontic nursing care format. Results: The results of nursing care on Ny. U was found that the client had fallen and sprained his leg two months ago. Currently the client feels pain in the left knee which is dislocated and looks swollen. Nursing diagnosis i.e. chronic pain related to physical injury agent Conclusion: The priority nursing problem for clients is pain can be overcome by giving warm compresses.